EHealth and Health Literacy: A Research Methodology Review. Issue 3 (1st April 2014) - Mackert, Michael; Champlin, Sara E.; Holton, Avery; Muñoz, Isaac I.; Damásio, Manuel José
Abstract: The development of e-health may provide powerful tools to improve health, but users' health literacy plays a role in their ability to make the most of e-health applications. This study reviewed research focused on e-health and health literacy, using content analysis to assess 95 articles from 2000 to 2010 to provide an overview of work done in this emerging field. Articles were coded for use of theory, research methods, and clarity of reporting study results. Findings indicate a lack of theory-driven design and evaluation of e-health applications, low use of established general health literacy measures, and interdisciplinary work with somewhat limited contributions by communication scholars. Implications for advancing this field of research are discussed.